Polyphenol rich oil palm leaves extract reduce hyperglycaemia and lipid oxidation in STZ-rats - Roslan Tan, Rosalina Tan; Mohammed, Suhaila; Fard, Samaneh Ghasemi; Mohamed Mustapha, Noordin; Goh, Yong Meng; Abd Manap, Mohd Yazid (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
Diabetes mellitus is a degenerative disease affecting about 25% of people over 40 years and is a risk factor for cardiovascular disease. The oil palm (Elaies guineensis) leaf is a major waste of the palm oil industry, which is among the top vegetable oil industry in the world. This study aims to evaluate the potential anti-diabetic effects of Oil palm leaves (OPL) ethanolic extract on normal and streptozotocin (STZ)-induced hyperglycaemic rats. OPL were administered orally at 50, 100 and 200mg per kg body weight/day) to Sprague Dawley rats and monitored for its glycaemic, lipidemic and antioxidant modulating effects. The Oil palm leaves (OPL) ethanolic extract treatment dose-dependently reduced blood glucose and oxidation in the STZ rats, and restored antioxidants enzymes levels. The optimum dose was 100mg/kg, which effectively reduced liver and kidney damage to the level of normal rats. This is the first study on dietary OPL ethanolic extract ability to modulate physiological responses and show organ protective effects against tissue damage in STZ-induced chronic hyperglycaemic rats. At the doses used OPL showed no adverse or chronic toxicity effects in these rats, indicating its potential use as a new functional food ingredient.